PENGARUH PENERAPAN STRATEGI PEMECAHAN MASALAH DALAM PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI KELAS VII SMP NEGERI 34 PEKANBARU - Isti Fauziah; Sehatta Saragih; Suhermi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research based on the importance of problem solving student ability. Due that thing, teacher should teach the student how to solve the problem, in order to have problem solving ability. This is a pre-experimental research using the Static Group Comparison design, which aims to whether the implementation of a problem solving strategy in cooperative learning type STAD giving good effect to problem solving student ability. This research was implemented in seventh grade SMP Negeri 34 Pekanbaru on first semester academic year 2016/2017. Population in this research is student in seventh grade SMP Negeri 34 Pekanbaru. Sample in this research consist of 69 stundents. A sample determine by purposive sampling’s technique, there had been selected the VII3 into class experimental and VII4 into class control. Class experimental was applied problem solving strategy in cooperative learning type STAD and class control was applied cooperative learning type STAD. Data in this research consist of data from the beginning problem solving ability’s test before given treatment which used to choose sample and data from problem solving ability’s test which used to collecting score from problem solving ability’s test. Collecting the data was done by giving test and documentation. The result of this research shows that implementation of problem solving strategy in cooperative learning type STAD give good effect to problem solving student ability.Key Word : Problem Solving Strategy, Cooperative Learning Type STAD, Matemathical Problem Solving Ability